Agronomic behavior of improved genotypes of broccoli (Brassica oleracea L. Var. Itálica) according to plantation distance - Checa, Oscar Eduardo; Ortega, Herlin Sebastián; Mora, Vicente Andrés (Revista de Ciencias Agrícolas, 2012)
The study was conducted at the property known Tutachag, Tuquerres municipality, Nariño department. Five genotypes were evaluated improved broccoli (Altar, Coronado, Monaco, Marathon and Legacy) and a traditional genotype used in the region (Decicco), applying three plant spacing 0.30 x 0.40 0.40 x 0.40 and 0.50 x 0.40 m. It employed a randomized block design with a 6 x 3 factorial arrangement with three replications, evaluating the weight of head diameter and yield. Determined that in terms of weight, headaches, improved genotypes that altar, Coronado, Monaco and Marathon Legacy with distances of 0.30 x 0.40, statistically behaved like one another, unlike the traditional variety Decicco, which presented the lowest averages, for distances of 0.40 x 0.40 mand 0.50 x 0.40 m, also in this variable there were no differences in genotypes. For head diameter at distances of 0.30 x 0.40, 0.40 x 0.40 mand 0.50 x 0.40 m, not statistically different between genotypes improved Altar, Coronado, Monaco and Marathon Legacy only statistical differences exist with the traditional genotype Decicco. In performance terms the Altar improved genotypes, Coronado, Monaco and Marathon Legacy distance of 0.30 x 0.40 are statistically similar, presenting statistical difference only with the traditional genotype Deccico; at distances of 0.40 x 0.40 m 0.50 x 0.40 there were no statistical differences between genotypes. The economic analysis was established that the genotype Legacy improved in the distance of 0.30 x0.40 m. presented the best economic performance, which increase the costs to $ 694,444 per hectare, have an increase in net income of $ 10,023,986 per hectare, showing a TRM of 1443.45%.